Chitosan‐g‐Polyester Microspheres: Effect of Length and Composition of Grafted Chains. Issue 10 (21st August 2019) - Demina, Tatiana S.; Sevrin, Chantal; Kapchiekue, Carmen; Akopova, Tatiana A.; Grandfils, Christian
Abstract: Hydrophobic segments made of oligo(l, l ‐ ord, l ‐lactides) or poly(l, l ‐lactide) are grafted onto chitosan backbone in order to use their amphiphilic behavior to prepare degradable microcarriers intended to be used for tissue engineering. Hydrophilic–lipophilic balance of these copolymers is adjusted playing on the respective length of their hydrophilic and hydrophobic moieties. Thanks to their self‐emulsifying properties, these graft copolymers are processed into microspheres in the absence of hydrophilic emulsifier commonly added in the aqueous phase of the oil/water emulsion. The copolymers containing amorphous oligolactide segments of medium length are demonstrated to be the most effective ones for microparticle fabrication. The microparticles are characterized using SEM, EDX, and FTIR. The reactivity of amine group is demonstrated using fluorescein isothiocyanate staining. The resulting microspheres disclose a porous core and a shell enriched by the hydrophilic polysaccharide moieties. Stabilization of the oil/water interface during the microsphere fabrication, total yield, size distribution, and microparticle surface morphology are mainly affected by the macromolecular features of the copolymers. Abstract : Microspheres from chitosan–polylactide copolymers having various lengths of their hydrophilic and hydrophobic moieties are fabricated by the emulsion solvent evaporation technique. These copolymers are able to stabilize oil/water interface during microparticle fabrication and in the absence of any emulsifiers in aqueous phase. Microparticles are recovered with high total yield and with controlled surface/bulk morphology and chemistry.